If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 11 = -80 + -9x Reorder the terms: 11 + 4x = -80 + -9x Solving 11 + 4x = -80 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. 11 + 4x + 9x = -80 + -9x + 9x Combine like terms: 4x + 9x = 13x 11 + 13x = -80 + -9x + 9x Combine like terms: -9x + 9x = 0 11 + 13x = -80 + 0 11 + 13x = -80 Add '-11' to each side of the equation. 11 + -11 + 13x = -80 + -11 Combine like terms: 11 + -11 = 0 0 + 13x = -80 + -11 13x = -80 + -11 Combine like terms: -80 + -11 = -91 13x = -91 Divide each side by '13'. x = -7 Simplifying x = -7
| 1+3w=10 | | x^6-5x^3-6=0 | | 6x+3-2x+6= | | 8Z+9=25 | | x^3+7x^2+12x=0 | | -50+5=45 | | g=cst | | h=3w | | 58-2x=16x+24 | | 16-5x=10-8x | | 158-6x=6x+14 | | 3.5b-8=4 | | 4x+34=12x-46 | | x+6y=1600 | | 2x+4y=1600 | | 3x^2+8x=-5 | | 12y+3=9y-15 | | 40x^3-180x=0 | | 4(-3)-3(-7)=19 | | (-3)+2(-7)=1 | | 2(4)+(5)=3 | | (4)-6(5)=-26 | | (2)-(-1)=5 | | 3(2)+(-1)=3 | | 3(7x+4)=6(3x+4) | | k^3-6k^2+12k-8=0 | | 4(5x+2)=9(2x+2) | | 4(4x+1)=3(5x+4) | | 5(2x+3)=3(3x+6) | | 6(2x-2)+3(2x+5)=30 | | 8(4x+1)+3(2x-3)=21 | | 2(3x+1)+4(6x+2)=4 |